Weekly chemotherapy with docetaxel/cisplatin/5-fluorouracil (TPF) for tretment of patien - Grašič Kuhar, Cvetka; Vogrin, Andrej; Zakotnik, Branko (Anali PAZU, 2022)
Patients with relapsed or metastatic squamous cell head and neck cancer in good performance status could be treated with cisplatin, 5-fluorouracil (and cetuksimab) in three-weekly cycles. Patients in poor performance status are treated with methotrexate monochemotherapy resulting in lower response rate and shorter survival. At our institution we treated patients in poor performance status with weekly TPF chemotherapy (docetaksel 20 mg/m2, cisplatin 20 mg/m2 in 5-fluorouracil 350 mg/m2 intravenously). Results were analysed retrospectively. Fifteen patients aged 45-78 years (median age 60 years) were treated. Median follow-up was 9.5 months. Patients received median 9 (min 4-max 15) weekly applications of chemotherapy. Eightyseven percent of patients had clinical benefit (complete remission - 2 pts, partial remission - 6 pts, stable disease - 5 pts). Median progression free survival was 6.2 months, median overall survival was 11.1 months. Hematological toxicity was low (one grade 3 neutropenia, no febrile neutropenia, 12 infective episods in 8 patients, 4 hospitalizations due to infection). Among nonhematological toxicity we recorded one grade 3 diarrhea. In two patients the dose of chemotherapy need to be adjusted. One sudden death occured. Weekly TPF chemotherapy was well tolerated. Efficacy and progression free survival are encouraging for patients in poor performance status.